Development and Content Validation of a Transcultural Instrument to Assess Organizational Readiness for Knowledge Translation in Healthcare Organizations: The OR4KT - Marie-Pierre Gagnon; Randa Attieh; Sandra Dunn; Gonzalo Grandes; Paola Bully; Carole A Estabrooks; France Légaré; Geneviève Roch; Mathieu Ouimet (Kerman University of Medical Sciences, 2018)
Background Implementing effective interventions in healthcare requires organizations to be ready to support change. This study aimed to develop, adapt transculturally, and assess the content and face validity of the Organizational Readiness for Knowledge Translation (OR4KT) tool. The OR4KT was designed to measure the readiness of healthcare organizations to implement evidence-informed change across a variety of services. Methods Based on systematic reviews of the literature, a Delphi exercise, and expert consultation, we first generated an initial pool of items. Second, we developed and assessed content validity of the pilot OR4KT questionnaire in English. Third, we created French and Spanish versions using a sequential forward and backward translation approach, and transcultural adaptation by a consensus process. Finally, we conducted pilot studies in three contexts - the Basque country region (Spain), and the provinces of Québec and Ontario (Canada) - where 30 experts assessed the face validity of the three versions of OR4KT. Results We selected 59 items, grouped in 6 dimensions (organizational climate, context, change content, leadership, organizational support, and motivation) for the final English version of OR4KT. Translation and transcultural adaptation did not identify any content or language problems. Our findings indicate that the English, French and Spanish versions of OR4KT are linguistically equivalents and have high face validity. Only minor revisions to the wording of some items were recommended. Conclusion The OR4KT holds promise as a measure of readiness for knowledge translation (KT) in healthcare organizations. The validity and reliability of the three versions of the OR4KT will be assessed in real-life contexts of implementation of evidence-based changes in healthcare.